Recruiting and retaining participants in three randomised controlled trials of psychological interventions conducted on acute psychiatric wards: top ten tips for success. Issue 4 (7th July 2022) - Jacobsen, Pamela; Haddock, Gillian; Raphael, Jessica; Peak, Craig; Winter, Rachel; Berry, Katherine
Abstract : Background: It is essential to conduct randomised controlled trials of psychological interventions on acute psychiatric wards to build a robust evidence base for clinical practice. Aims: This paper aims to share strategies from three different in-patient trials that successfully recruited and retained participants, to disseminate good practice for the conduct of future trials in this challenging and complex clinical setting. Method: We present strategies from three in-patient trials of psychological interventions: TULIPS (Talk, Understand, Listen for Inpatient Settings), amBITION (Brief Talking Therapies on Wards) and INSITE (Inpatient Suicide Intervention and Therapy Evaluation). All studies recruited participants from acute in-patient wards, initiated therapy within the in-patient setting and followed up on participants post-discharge. Results: We summarise our recommendations for good practice in the form of ten top tips for success, based on our collective experience of conducting trials on psychiatric wards. Key themes relate to the importance of relationships between the research team and clinical staff; good stakeholder involvement and getting early buy-in from the team; and adapting to the particular demands of the clinical setting. Conclusions: Sharing good practice recommendations can help reduce research waste arising from poor recruitment and/or retention in future in-patient clinical trials.